Міжнародні та національні кодекси поведінки публічних службовців - Лавров Дмитро Олександрович (My University, 2023)
Досліджено суспільно-політичні погляди на етичні стандарти поведінки публічних службовців. Визначено обов’язки публічних службовців Загальними правилами етичної поведінки. Виявлено особливості використання публічними службовцями свого службового становища. Проаналізовано міжнародні стандарти дотримання етичних норм в державно-службових відносинах. Надано методичні рекомендації щодо удосконалення етичних норм поведінки публічних службовців. Розроблено шляхи впровадження етичних стандартів як дієвого механізму формування моральності державних службовців. Ключові слова: етична поведінка, публічний службовець, кодекс, етичні стандарти, моральність, механізм.

Socio-political views on the ethical standards of behavior of public servants have been studied. The duties of public officials are defined by the General Rules of Ethical Conduct. Peculiarities of public servants' use of their official position have been revealed. International standards of compliance with ethical norms in public service relations are analyzed. Methodological recommendations on improving the ethical standards of behavior of public servants have been provided. Ways of implementing ethical standards as an effective mechanism for forming the morality of civil servants have been developed. Keywords: ethical behavior, public servant, code, ethical standards, morality, mechanism.
International and national codes of conduct for public servants